Using ultrasound for improving hydration and debittering of Andean lupin grains - Miano A.C. (2019)
This article presents results about the potential use of ultrasound technology on the hydration and debittering process of Andean lupin grains (Lupinus albus Sweet). The hydration process was conducted conventionally and also assisted by ultrasound technology (ultrasonic water bath, 25 kHz, 41 W/L). Further than the hydration kinetics, the alkaloid content was evaluated. As results, the hydration kinetics of this grain showed a sigmoidal behavior, which was accelerated almost 40% using ultrasound. The lag phase was reduced about 13%, and the equilibrium moisture content was increased about 14%. Finally, by using ultrasound during hydration process, the alkaloid extraction was also improved, extracting 21% more compared to the conventional process. It was concluded that ultrasound technology accelerates not only the hydration process but also the extraction of alkaloids. Practical Applications: Andean lupin is a pulse with potential importance for human and animal alimentation due to its high quantity of proteins. However, this pulse has a considerable quantity of undesirable alkaloids that are bitter and toxic. Therefore, a debittering process is required. Further, before debittering, hydration of the grains is required, which is a long and batch process. This work demonstrated that both the hydration and the debittering processes can be enhanced by ultrasound. Consequently, ultrasound technology would have a double application during hydration process of Andean lupin grains. © 2019 Wiley Periodicals, Inc.